2014
DOI: 10.21091/mppa.2014.4040
|View full text |Cite
|
Sign up to set email alerts
|

Metatarsal Pain and Plantar Hyperkeratosis in the Forefeet of Female Professional Flamenco Dancers

Abstract: The objectives of this study were to determine the frequency of metatarsal pain and of hyperkeratosis on the plantar forefoot in female professional flamenco dancers, and to determine whether there is a relationship between the two disorders. METHOD: Forty-four female professional flamenco dancers, with a minimum activity of 25 hrs/wk, participated in this cross-sectional study. The presence or absence of metatarsal pain while dancing was recorded, and plantar pressures were measured on a pressure platform, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
1
10
0
2
Order By: Relevance
“…We may hypothesize that athletes tend to lean forward or use fore-foot rather than rear-foot surface owing to the specifics of their sports. As mentioned before, several authors reported the same results when they compared athletes practising different sports, athletes practising the same sport, sedentary people, and people with different health problems [2,5,16,[29][30][31][32][33][34][35][36]. In our observations, sedentary participants showed more pressure in the fore-foot than in the rear-foot surface (50.39% and 49.61%, respectively).…”
Section: Discussionsupporting
confidence: 84%
“…We may hypothesize that athletes tend to lean forward or use fore-foot rather than rear-foot surface owing to the specifics of their sports. As mentioned before, several authors reported the same results when they compared athletes practising different sports, athletes practising the same sport, sedentary people, and people with different health problems [2,5,16,[29][30][31][32][33][34][35][36]. In our observations, sedentary participants showed more pressure in the fore-foot than in the rear-foot surface (50.39% and 49.61%, respectively).…”
Section: Discussionsupporting
confidence: 84%
“…Estos resultados son similares a los registrados por Vargas (2009) entre bailaoras profesionales de baile flamenco donde un 27.3% de las participantes manifestaban dolor tanto en pies como en rodillas. Por otro lado, Castilla-Cubero et al (2011) elevan hasta un 50% los casos dolor en rodillas y hasta un 61.45% en pies, mientras que Castillo-López et al (2014) encuentran el 80.7% de las bailaoras profesionales estudiadas manifestaban dolor metatarsal mientras bailaban y el 34.78% a nivel patelofemoral. Esta evidencia sobre los pies y rodillas como zonas más dolorosas está contrastada en otros estudios (Bejjani, 1987;Calvo, Alonso, Pasadolos, & Gómez-Pellico, 1998;Quer et al, 2004;Shybut et al, 2008) donde la acción de zapatear y el uso del zapato de tacón son las primeras causas.…”
Section: Discussionunclassified
“…Además, el calzado flamenco no está diseñado para absorber impactos ni las superficies de bailes siempre son las más idóneas (Castillo-López, Munuera-Martínez, Algaba-Guisado, Reina-Bueno, Salti-Pozo, & Vargas-Macías, 2016). Todo ello conlleva que más del 80% de las profesionales del baile flamenco presenten deformaciones de carácter podológico (Castillo et al, 2014).…”
Section: Discussionunclassified
“…9,31 A similar propensity of foot and ankle injuries has been noted with a high prevalence of podiatric medical problems in professional dancers. 4,5…”
Section: Discussionmentioning
confidence: 99%